IMPLEMENTASI STRATEGI LAYANAN BIMBINGAN DAN KONSELING KOMPREHENSIF BAGI SISWA TUNANETRA DI MTs YAKETUNIS YOGYAKARTA - Hayatul Khairul Rahmat (UIN Sunan Kalijaga Yogyakarta, 2019)
The purposes of this study is to determine the implementation of a comprehensive guidance and counseling service strategy for students with visual impairment in MTs Yaketunis Yogyakarta. This study used qualitative research methods. The data collection method uses interviews and documentation. Futhermore, the research subjects were counseling teachers at the MTs Yaketunis Yogyakarta. The results revealed the implementation of a comprehensive guidance and counseling service strategy for students with visual impairment in MTs Yaketunis Yogyakarta in general has been going well. This can be seen from the indicators that the counseling and counseling service strategy in schools includes four service components with each strategy in it, namely: First, basic services with classical guidance strategies, orientation services, information services, group guidance, and data collection. Second, responsive services use individual counseling strategies, group counseling, referrals, collaboration with subject teachers or homeroom teachers, collaboration with parents of students, collaboration with related parties outside of school, peer guidance, consultation, case conferences, and home visit. Third, individual planning with a placement and distribution service strategy. Fourth, system support uses strategies for network development, management activities, as well as research and development, and evaluation.